Evaluasi faktor penyebab terjadinya kecelakaan lalu lintas: studi kasus Jalan Raya Labuan-Pandeglang KM 18-27 - Dian Firdaus; M. Oka Mahendra; Hadi Wiguno (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
This study aims to collect factors causing traffic accidents and identify accident-prone locations (black spots) on the Labuan–Pandeglang Highway section KM 18-27. The study is limited to traffic accident data for the period 2020–2024 obtained from the local police, as well as the results of field surveys related to road geometric conditions and safety facilities. The analysis methods used are the Equivalent Accident Number (EAN), Upper Control Limit (BKA), and Upper Control Limit (UCL). The results show that there are three black spot segments, namely KM 18, KM 19, and KM 22, with EAN values ??exceeding the BKA (235) and UCL limits. The dominant factors causing accidents include lack of street lighting, dangerous geometric conditions (sharp bends and steep descents), driver non-compliance with traffic signs, unroadworthy vehicle conditions, and overloading. By enriching the literature analysis on black spots on national roads and strengthening the application of the EAN–BKA–UCL method in Indonesia, this study makes a scientific contribution. In addition, these findings are expected to be used as a basis for developing policies aimed at improving traffic safety through public education initiatives, law enforcement, and infrastructure improvements.